2010
DOI: 10.1026/0932-4089/a000026
|View full text |Cite
|
Sign up to set email alerts
|

Das Instrument zur Kodierung von Diskussionen (IKD)

Abstract: Das Instrument zur Kodierung von Diskussionen (IKD) ist ein neues und nutzerfreundliches Verfahren, mit dem Interaktionsprozesse in Organisationen zeitökonomisch kodiert werden können. Somit wird es möglich, eine größere Anzahl von Gruppen und Kommunikationssituationen (z. B. Entscheidungssitzungen, Teambesprechungen oder Mitarbeitergespräche) Akt für Akt standardisiert zu beobachten und zu analysieren. Mit dem IKD werden zwei Arten von Kommunikationsebenen gleichzeitig untersucht: die interpersonale und die f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…While previous coaching research, including nonverbal behavior in dyads (Schermuly et al, 2010;Ianiro et al, 2013Ianiro et al, , 2015Ianiro and Kauffeld, 2014) showed that the working alliance depended on the degree of dominance and affiliation of coach-client interactions, our study focused on the moderating role of the working alliance in the association between nonverbal synchrony and self-regulation toward goal attainment. While these previous coaching studies acknowledge the aspect of reciprocity as a key element of interpersonal theory (Kiesler, 1996) and thus converge with the theoretical framework of interpersonal synchrony (Feldman, 2007(Feldman, , 2015, they differ in their focus on affiliation and dominance and how these interpersonal factors impact on the working alliance in coaching.…”
Section: The Temporal Nature Of Nonverbal Synchrony In Goal Attainmentmentioning
confidence: 95%
See 1 more Smart Citation
“…While previous coaching research, including nonverbal behavior in dyads (Schermuly et al, 2010;Ianiro et al, 2013Ianiro et al, , 2015Ianiro and Kauffeld, 2014) showed that the working alliance depended on the degree of dominance and affiliation of coach-client interactions, our study focused on the moderating role of the working alliance in the association between nonverbal synchrony and self-regulation toward goal attainment. While these previous coaching studies acknowledge the aspect of reciprocity as a key element of interpersonal theory (Kiesler, 1996) and thus converge with the theoretical framework of interpersonal synchrony (Feldman, 2007(Feldman, , 2015, they differ in their focus on affiliation and dominance and how these interpersonal factors impact on the working alliance in coaching.…”
Section: The Temporal Nature Of Nonverbal Synchrony In Goal Attainmentmentioning
confidence: 95%
“…Our project extends previous coaching studies that have included the nonverbal channel by looking at the degree of dominance and affiliation in coach-client interactions (Schermuly et al, 2010;Ianiro et al, 2013Ianiro et al, , 2015Ianiro and Kauffeld, 2014). Specifically, we are interested in exploring the interplay between nonverbal synchrony, emotional as well as cognitive self-regulation, and their association with goal attainment in coaching.…”
Section: Introductionmentioning
confidence: 96%
“…The number of questions that the leader asked during the discussion was coded with the Discussion Coding System (DCS, Schermuly & Scholl, 2012;Schermuly, Schröder, Nachtwei, & Scholl, 2010). See Appendix for a more detailed description of the coding procedure.…”
Section: Question Asking By the Leadermentioning
confidence: 99%
“…Its accompanying interpersonal affect is coded on two dimensions: power (dominance vs. submissiveness) and affiliation (friendliness vs. hostility). The ratings on these dimensions are based on verbal and nonverbal cues as described in the DCS manual [21]. Examples include interrupting someone else or expressive gesticulation as markers for dominance.…”
Section: Video Annotationmentioning
confidence: 99%
“…All discussions were recorded on video and coded with the Discussion Coding System (DCS) [21]. The DCS is a state-of-the-art coding system to analyse group interaction.…”
Section: Video Annotationmentioning
confidence: 99%